Comprehensive Production Maintenance and its Role in Improving the Company Performance - Kareem, Jasim Mohammed; Alallaq, Hussein Adnan Essa; Alsaedi, Rafid Khudhur Radhi; Al-Jazaeri, Mohammed Basim Mohammed; Sabti, Yousif Mousa (South Asian Journal of Social Sciences and Humanities, 2023)
The study aimed to reveal the impact of applying comprehensive production maintenance on  company performance in small and medium industrial Malaysian companies. The descriptive  analytical secondary data was utilised as a tool for gathering data from 135 companies as a  sample from 2009 to 2017, and after conducting the analysis of the data and testing the  hypotheses, the study reached a number of results among them. There is a positive significant  effect of the application of comprehensive productivity maintenance on company performance  in in the small and medium industrial companies. Therefore, this study recommended that the  total productive maintenance is a system that is also valuable for quality administration and  safety administration in rapports of keeping the integrity of equipment and operating  approaches. The study recommended giving more attention to the management of the industrial  companies.
Keywords: Comprehensive production maintenance; company performance; small and medium industrial companies